1987
DOI: 10.1007/bf00570916
|View full text |Cite
|
Sign up to set email alerts
|

Normal serum activities of some diagnostic enzymes in dromedary camel in Sudan

Abstract: 76 adult camel (30 males and 46 females) sera were surveyed for the normal activities of alkaline phosphatase (ALP), alanine aminotransferase (ALT), aspartate aminotransferase (AST), creatine phospho-kinase (CPK), gamma-glutamyl transpeptidase (GGT) and lactate dehydrogenase (LDH). The values recorded for the above enzymes were compared to other data in the literature.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

1991
1991
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 1 publication
0
3
1
Order By: Relevance
“…Serum mean AST activity of this study is higher than the maximum value of Najdi camels (Haroun, 1994). Higher values for serum AST activity were found in Sudan (Eldirdiri et al, 1987) and in Saudia Arabia (Osman and Al-Busadah, 2001). Serum activity of ALP compares favorably with the finding of Osman and Al-Busadah, (2001) for dry female camels.…”
Section: Discussioncontrasting
confidence: 53%
See 1 more Smart Citation
“…Serum mean AST activity of this study is higher than the maximum value of Najdi camels (Haroun, 1994). Higher values for serum AST activity were found in Sudan (Eldirdiri et al, 1987) and in Saudia Arabia (Osman and Al-Busadah, 2001). Serum activity of ALP compares favorably with the finding of Osman and Al-Busadah, (2001) for dry female camels.…”
Section: Discussioncontrasting
confidence: 53%
“…Haematological and serum biochemical values can be useful for evaluating the health of the population of captive and freeliving camels. Haematological and serum biochemical values for Sudanese camels have been studied by many author (Hassan et al, 1968, Eldirdiri et al, 1987and Wahbi et al, 1980. However, the information is fragmented and incomplete because the origin (captive or freeliving), sex and age, or diet of the animals was not indicated.…”
Section: Introductionmentioning
confidence: 99%
“…In scimitar-horned oryx, on the other hand, Bush et al (1983) found no variations in alkaline phosphatase activity with sex. Eldirdiri et al (1987), in their study on dromedary camels, found higher alkaline phosphatase levels in females. In view of these contradictory results and considering the small number of males examined in our study we conclude that the difference found by us between male and female mountain reedbucks are within the range of normal alkaline phosphatase activity of this species.…”
Section: Discussionmentioning
confidence: 90%
“…Levels of circulating enzymes can be useful as an aid in the diagnosis of certain diseases (Eldirdiri et al, 1987). Biochemical analysis of serum can often provide valuable information regarding cardiovascular health and illness in animals (Coodley, 1970).…”
Section: Introductionmentioning
confidence: 99%